Sistem Informasi Manajemen Berbasis Website Untuk Memfasilitasi Pengolahan Data Perusahaan Studi Kasus: Bong Tailor - Dzaky Abby Fauzan Aziz; Mohammad Mausa Gani; Arif Rachmat Darmawan; Muhammad Naufal Malikulmulki; Hidayat Hidayat (Majalah Ilmiah UNIKOM, 2024)
The Bong Tailor garment business is known for its high-quality products and reliable services. However, the growth of this business has led to the complexity of processing production, sales, and customer data. Manual processing with record books increases the risk of errors and the loss of essential data. Therefore, the need for an integrated Management Information System (MIS) has become more urgent. This article aims to discuss the importance of investing in a web-based MIS connected to a Database Management System (DBMS) using PHP. The research methodology involves requirement analysis, technology selection, and system design. It is expected that this article provides an understanding of the benefits of integrating information technology in the garment business. The research findings show that the implementation of the MIS can enhance the operational efficiency of Bong Tailor through the automation of production, sales, and customer data processing. Additionally, the MIS optimizes data storage by safeguarding against the risk of data loss or damage. In conclusion, web-based MIS integration with DBMS is a crucial step for Bong Tailor to address the increasingly complex data processing challenges. This investment brings benefits in terms of operational efficiency, customer interaction, data-driven decision-making, and overall data processing. Key Words: data processing, database management system, management information systems, websites